Every girl tells a story : a celebration of girls speaking their minds - Jones, Carolyn (Carolyn Elizabeth); Girl Scouts of the United States of America (New York : Simon & Schuster Books for Young Readers, 2002)
Presents the attitudes and achievements of a diverse group of girls between the ages of thirteen and eighteen living across the United States through portraits and their own words
Keywords: Teenage girls -- United States -- Case studies; Girls -- United States -- Case studies; Teenage girls